2016
DOI: 10.1016/j.ijchp.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining age-related differences in support needs on the Supports Intensity Scale-Children's Version-Spanish translation

Abstract: Background: Interest in the support needs of people with intellectual disability has directed attention to developing assessments to measure of the pattern and intensity of supports which people need to participate in valued life activities. Assessments of the support needs of children must account for the influence of age. Method: Four hundred fifty (450) Spanish children with intellectual disability (ages 5-16) were assessed with the SIS-C Spanish. To test for measurement invariance and latent differences, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This ceiling effect was observed for the seven scales. It does not seem to be related to the age or gender of the participants, supporting the decision to use the same set of items for all age bands, as suggested in previous research [44][45][46]. The probability of being observed in the low discrimination range strongly depended on the level of ID given that, on average, 87% of the cases located in the ceiling effect area had severe/profound ID.…”
Section: Discussionsupporting
confidence: 77%
“…This ceiling effect was observed for the seven scales. It does not seem to be related to the age or gender of the participants, supporting the decision to use the same set of items for all age bands, as suggested in previous research [44][45][46]. The probability of being observed in the low discrimination range strongly depended on the level of ID given that, on average, 87% of the cases located in the ceiling effect area had severe/profound ID.…”
Section: Discussionsupporting
confidence: 77%
“…Shogren et al () found a general decrease in the intensities of support needs of children with intellectual disability for each age cohort. Giné et al () and Verdugo, Arias, et al () found different results but a similar trend: The differences in the intensities of support needs tended to be concentrated in the means of younger (5–10 years) and older children (11–16 years) with intellectual disability, with the latter showing a decrease in such intensity. On the other hand, for the typically developing children, there was a slight general decreasing trend in the latent means for all the factors across the six age cohorts (this trend was stronger for HLA, CNA and SPA).…”
Section: Resultsmentioning
confidence: 87%
“…This means that the possible role that adaptive behaviour has in explaining the differences found in the support needs scores between groups could not be empirically verified, and further research is necessary. On the other hand, the present authors are aware of the importance of age regarding support needs assessment in children with intellectual disability, in the sense that older children have less intensity of support needs and vice versa (Shogren et al, ; Verdugo, Arias, et al, ). Indeed, Thompson and Viriyangkura () suggest the need for comparing the support needs of children with intellectual disability with the support needs of their same age typically developing peers as the best way to determine how extraordinary and non‐extraordinary support needs differ in children.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The influence of age on support needs has been researched in at least 13 studies, with three of them having it as the primary focus [ 49 , 82 , 103 ]. Support needs decrease as the child grows [ 82 ], with more significant differences between the 5–10 and 11–16 age cohorts [ 33 , 49 , 97 , 102 , 103 ]. However, during the transition stage to adult life, between 16 and 22 years of age, support needs are again higher and present great variability, suggesting the need to evaluate supports and make effective plans in this period [ 79 , 81 ].…”
Section: Resultsmentioning
confidence: 99%